Etnobotani tumbuhan obat Solanaceae pada masyarakat suku Kerinci di wilayah Lempur Kabupaten Kerinci Provinsi Jambi - Azzikri Azzikri; Singgih Tri Wardana; Harmida Harmida (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2020)
The Kerinci tribe is a traditional community that has long had close interactions with the living natural resources and its ecosystem. The lempur region is the oldest area in kerinci which is inhabited by native Kerinci tribes. Research on ethnobotany of medicinal plants in this region is still very small because there are still a number of villages that have not yet been explored and documented. Therefore, it is necessary to conduct a study to obtain data and information on the ethnobotany of medicinal plants in this region. The purpose of this study was to determine the diversity of medicinal plant species and how to use the Zingiberaceae medicinal plant by the Kerinci tribe in the Lempur region. The research method was carried out using descriptive method through field observations and interviews. Based on the research that has been done, there are 5 types of medicinal plants Solanaceae. The benefits of this plant can treat diseases such as, sore eyes, blood booster disease, hypertension, asthma, and stomach ache.